2021
DOI: 10.1371/journal.pone.0260031
|View full text |Cite
|
Sign up to set email alerts
|

Expanding or shrinking? range shifts in wild ungulates under climate change in Pamir-Karakoram mountains, Pakistan

Abstract: Climate change is expected to impact a large number of organisms in many ecosystems, including several threatened mammals. A better understanding of climate impacts on species can make conservation efforts more effective. The Himalayan ibex (Capra ibex sibirica) and blue sheep (Pseudois nayaur) are economically important wild ungulates in northern Pakistan because they are sought-after hunting trophies. However, both species are threatened due to several human-induced factors, and these factors are expected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 74 publications
2
30
0
Order By: Relevance
“…This results in the isolation and decrease in their resistance to climate change or human-induced change [39,40]. One of the most common recommendations for protecting biodiversity is to increase connectivity and create ecological networks that connect natural habitats [41], a conservation practice that is becoming even more relevant in the face of impending climate change [5,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…This results in the isolation and decrease in their resistance to climate change or human-induced change [39,40]. One of the most common recommendations for protecting biodiversity is to increase connectivity and create ecological networks that connect natural habitats [41], a conservation practice that is becoming even more relevant in the face of impending climate change [5,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…We found that saturated O 2 , range sea surface temperature, salinity, primary productivity, and pH play little role in shaping this complex distribution supporting previous findings that these variables have little contribution in predicting richness of mangrove crabs 23 . Climate change is known as a major driver of biodiversity loss worldwide 18,[53][54][55] . Previous studies have shown that marine species will be negatively affected by climate change 53,[56][57][58] .…”
Section: Discussionmentioning
confidence: 99%
“…Species Distribution Models (SDMs) help to evaluate habitat suitability and are key to estimating risk to species by understanding potential vulnerabilities and what landscape and climate variables contribute most to their distribution (Wang et al, 2020). These tools can also be useful for predicting species' responses to future climate and environmental change (Beest et al, 2021; Pang et al, 2021), which is especially important for climatically constrained species, such as those that live in mountainous areas (Ali et al, 2021; Rahbek et al, 2019; Xenarios et al, 2019).…”
Section: Introductionmentioning
confidence: 99%